2015
DOI: 10.1016/j.ttbdis.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Roe deer sera used for TBE surveillance in Austria

Abstract: A large majority of Austrian citizens are aware of tick-borne encephalitis (TBE), consequently reflected by a high vaccination rate of 85%. In return, risk assessment and disease mapping on human cases might be hampered due to high and inhomogeneous vaccination rates and travel habitats of humans. The roe deer was used to obtain a starting point for the integral view on the actual risk of TBE in Austria. The roe deer exhibits several attributes which makes it suitable as an indicator species: the roe deer has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2109
2109

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This study found positive animals in known endemic areas but also helped to map new risk areas for TBE. Other recent studies in roe deer have revealed varying prevalences: in Germany, 10% (Balling et al, ), in the Netherlands, 2% (Jahfari et al, ), in Austria, 2.4% (Duscher, Wetscher, Baumgartner, & Walder, ) and in Belgium 5.1% (Tavernier et al, ). In our study, one sample (0.7%) was TBE positive.…”
Section: Discussionmentioning
confidence: 95%
“…This study found positive animals in known endemic areas but also helped to map new risk areas for TBE. Other recent studies in roe deer have revealed varying prevalences: in Germany, 10% (Balling et al, ), in the Netherlands, 2% (Jahfari et al, ), in Austria, 2.4% (Duscher, Wetscher, Baumgartner, & Walder, ) and in Belgium 5.1% (Tavernier et al, ). In our study, one sample (0.7%) was TBE positive.…”
Section: Discussionmentioning
confidence: 95%
“…TBEV-infected areas are preferably identified through TBEV-specific antibodies in sentinel species ( 13 ). Roe deer have small home ranges, are often infested with I. ricinus ticks, seroconvert well ( 14 , 15 ), and are proven good sentinel species ( 1 , 14 , 15 ). However, if one considers serologic cross-reactivity among flaviviruses, potential foci identified need to be confirmed by other methods, such as PCRs for detecting TBEV in ticks from these sites ( 1 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission foci are mostly restricted to small areas and the detection of these foci is limited by the numbers of ticks sampled as well as the sampling locations. For accurate determination of TBEV foci, a very small meshed sampling design is needed ( 52 ). Additionally, the virus load in ticks can be below the detection limit ( 53 ); therefore, the lack of TBEV in the ticks in this study does not confirm the absence of TBEV in the sampling area.…”
Section: Discussionmentioning
confidence: 99%